12 immigrants who made American science great - Poehlmann, Tristan; 12 Story Library (Firm) (Mankato, MN : 12-Story Library, 2018)
America is a nation of immigrants whose contributions gave us America, and taught us what it means to be free. This book profiles three pre-1950 scientists and another nine contemporary scientists (12 profiles); in a biography examinging where they came from, and their notable contribution(s) in America. From Croatia's Nikola Tesla who helped design electrical systems, to Germany's Maria Goeppert Mayer who studied the atomic nucleus, to Austria's Hedy Lamarr who invented a radio guidance system for torpedos, this book will inspire readers with stories of possibility and grit.and emphasizes how they made our country great. Backmatter includes 4 extra mini-bios of other amazing American citizens who we never think of as immigrants. Note the additional and up-to-the minute resources available at 12StoryLibrary.com: Editor-selected news articles; videos; online resources; teacher resources; live Twitter and RSS feeds.
Includes bibliographical references (page 31) and index.
Keywords: Scientists -- United States -- Biography; Immigrants -- United States -- Biography; Biographies